A framework for analysing interoperability in electronic government. (24th January 2011) - Solli-Sather, Hans
E-government interoperability has been recognised to have a potentially great impact on productivity and user satisfaction. Based on the stage hypothesis model of growth in e-government interoperability, a framework to analyse and predict interoperability is suggested. Lessons learned from the experiences of the government sector in Norway are useful in analysing the number of stages, dominant problems at each stage, evolutionary path, and the economies of interoperability. Using the organisational, semantic and technical parameters of the framework, benchmarks applicable to each stage are applied to the case studies. Findings indicate that governments face different issues, expectations and benefits, depending on their maturity level.